Monoclonal antibodies specific for Shigella flexneri lipopolysaccharides: clones binding to type I and type III:6,7,8 antigens, group 6 antigen, and a core epitope. - Carlin, N I (1986)
Monoclonal antibodies against the Shigella flexneri lipopolysaccharide (LPS) were generated in two fusions by using the myeloma cell line Sp2/0 as a fusion partner with spleen cells from BALB/c mice immunized with S. flexneri serotypes 1b and 3a bacteria. The antibodies were characterized by immunoblotting, enzyme-linked immunosorbent assay (ELISA), hemagglutination, and coagglutination. Four different types of monoclonal antibodies were isolated: antibodies specific for the core antigen of the LPS, antibodies specific for the type I O antigen, antibodies specific for the group 6 O antigen, and antibodies specific for the type III:6,7,8 O antigen. The core-specific antibodies were shown to be specific for the Escherichia coli R3 core, which all S. flexneri LPSs tested, except for S. flexneri serotype 6 LPS, have. The type I O antigen-specific antibodies were shown to bind exclusively to S. flexneri serotypes 1a and 1b in ELISA. The type III:6,7,8 O-antigen-specific antibodies were specific for S. flexneri serotype 3a in ELISA and hemagglutination. Two different group 6 O-antigen-specific antibodies were bound. One was bound in both ELISA and hemagglutination to LPSs of S. flexneri serotypes 1b, 3a, 3b, and 4b, whereas the second was bound only to LPSs of serotypes 3a, 3b, and 4b in ELISA but to LPSs of all four serotypes in hemagglutination. The specificity of the isolated I, III:6,7,8, and group 6 monoclonal antibodies was verified by coagglutination of 363 S. flexneri clinical isolates.